Pengaruh Iklan dan Harga Terhadap Keputusan Pembelian Pada Aplikasi Gojek - Ahmad Alim Rasyidi; Tundung Subali Patma (Pusat Riset dan Inovasi Nasional, 2024)
Go-Food is the most popular food delivery service in Indonesia with the largest number of users. Go-Food seeks to develop effective advertising to increase consumer awareness of food delivery services. On the other hand, price is an important factor in influencing the affordability and attractiveness of these services for students. This research aims to analyze how advertising and price influence Go-Food purchasing decisions among D4 Marketing Management students at Malang State Polytechnic. Quantitative research uses two independent variables: advertising and price and purchasing decisions as dependent variables. Using incidental sampling approaches, 75 respondents were given questionnaires to complete in order to obtain data. Multiple linear regression analysis together with hypothesis testing is the analytical technique employed. Promotion and price have a favorable and considerable impact on purchasing decisions, according to the outcomes of data analysis conducted through hypothesis testing. This research hopes that Gojek can provide the latest innovations for its advertising so that it can fulfill consumers' culinary tastes and desires for purchasing Go-Food and is expected to increase intensity and quantity in providing discounts in order to attract the attention of potential consumers.